2006
DOI: 10.1210/en.2006-0760
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of White Adipose Tissue after Retinoic Acid Administration in Mice

Abstract: A reduced brown adipose phenotype in white adipose tissue (WAT) may contribute to obesity and type 2 diabetes in humans. Retinoic acid, the carboxylic form of vitamin A, triggers in rodents a reduction of body weight and adiposity and an increased expression of uncoupling proteins in brown adipose tissue and skeletal muscle. In this study, we investigated possible remodeling effects of all-trans retinoic acid (ATRA) in WAT depots. Changes in the expression of genes related to thermogenesis and fatty acid oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
190
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(220 citation statements)
references
References 41 publications
26
190
2
2
Order By: Relevance
“…It has been shown that retinoic acid in vivo induces a recruitment of multilocular cells in mouse WAT, but stimulates more the expression of the oxidative enzymes than that of UCP1. 36 Altogether, the different modulation patterns of BAT B and WAT B adipocytes confirm a different nature of the two cell types. They are in agreement with the results of Coulter et al 16 showing that fundamentally different regulatory mechanisms exist to control the thermogenic capacities of these tissues.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that retinoic acid in vivo induces a recruitment of multilocular cells in mouse WAT, but stimulates more the expression of the oxidative enzymes than that of UCP1. 36 Altogether, the different modulation patterns of BAT B and WAT B adipocytes confirm a different nature of the two cell types. They are in agreement with the results of Coulter et al 16 showing that fundamentally different regulatory mechanisms exist to control the thermogenic capacities of these tissues.…”
Section: Discussionmentioning
confidence: 86%
“…To the best of our knowledge, only studies dealing with all-trans RA have been published. These studies showed that both in in vivo (in treated mice) and mature 3T3-L1 adipocytes, all-trans RA triggered remodelling to reduce lipogenesis and increased oxidative metabolism, as shown by gene expression changes, histological changes and in the case of cultured cells, increases in lipolysis and fatty acid oxidation [50,51].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…9,10 Retinoic acid (RA), its acid form, potently blocks adipogenesis of cultured preadipose cells when introduced at early stages of the differentiation process, 11 although other reports indicate that RA at low doses may in fact promote adipogenesis. [12][13][14] Studies in adult rodents treated with RA [15][16][17][18][19][20][21][22][23] or retinaldehyde 24 sustain an antiadiposity action of vitamin A derivatives in vivo. Furthermore, results from animal studies 16,[25][26][27][28] and human observational studies 29,30 point to an inverse relationship between vitamin A status and body fat content.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, results from animal studies 16,[25][26][27][28] and human observational studies 29,30 point to an inverse relationship between vitamin A status and body fat content. The antiadiposity action of RA has been traced to increased fatty acid oxidation and energy expenditure in adipose tissues, 15,19,21,31 skeletal muscle 20,32 and the liver, 33 and to reduced peroxisome proliferator-activated receptor g (PPARg) levels and activity in white fat. 16,34,35 PPARg is a nuclear receptor transcription factor key for adipogenesis and also required for lipogenesis and survival in mature adipocytes.…”
Section: Introductionmentioning
confidence: 99%